HISTORY AND IMPACTS OF THE PARINTINS MATHEMATICS OLYMPIAD (OPM): A JOURNEY OF LEARNING, CHALLENGES, AND ACHIEVEMENTS - Nunes, Débora da Silva; Beltrão, Isabel do Socorro Lobato; da Fonseca, Júlio Cezar Marinho; Fonseca, Maildson Araújo; Rendeiro, Manoel Fernandes Braz; Rodrigues, Pedro Silvio Coimbra; da Silva, Paulo Sergio Ribeiro (Seven Editora, 2025)
This article aims to present the development, challenges, and achievements of the Parintins Mathematics Olympiad (OPM). To this end, we sought to analyze the historical trajectory of the OPM since its inception, identifying its pedagogical, social, and institutional impacts on the development of mathematics education in the municipality of Parintins. The methodological approach adopted was qualitative, descriptive, and historical-documentary in nature, also configured as a case study. The research was conducted through interviews with the founder of the competition, as well as the analysis of official documents and records from previous editions of the event. The object of study is the trajectory of the Parintins Mathematics Olympiad from 2004 to 2024. The results obtained throughout the analyzed period indicate that the OPM has played a fundamental role in strengthening mathematics education in Parintins. Since its creation, the number of participating schools has grown significantly, encompassing both urban and rural areas. Among the main challenges faced are the maintenance of continuous financial support, the expansion of participation from rural schools, and the need to consolidate a permanent network for teacher training linked to the project.DOI: https://doi.org/10.56238/sevened2025.038-026